Editor's Highlight: Placental Disposition and Effects of Crizotinib: An Ex Vivo Study in the Isolated Dual-Side Perfused Human Cotyledon. (24th March 2017) - Eliesen, Gaby A.M.; van den Broek, Petra; van den Heuvel, Jeroen J.; Bilos, Albert; Pertijs, Jeanne; van Drongelen, Joris; Russel, Frans G.M.; Greupink, Rick
Abstract: Tyrosine kinase inhibitors (TKIs) play an important role in cancer pharmacotherapy, yet there is limited data on their use during pregnancy. We studied placental disposition and placental toxicity of crizotinib, a TKI used to treat nonsmall cell lung cancer. Term placentas were perfused for 3 h with crizotinib (1 µM) using the ex vivo dual-side cotyledon perfusion technique. Interference of TKIs with trophoblast viability was studied using BeWo cells. Expression of P-glycoprotein (P-gp) and Breast Cancer Resistance Protein (BCRP) in placental tissue was assessed by immunohistochemistry and inhibition of these transporters was determined in vitro by transport studies with membrane vesicles overexpressing human P-gp or BCRP. We found that crizotinib rapidly and strongly accumulates in cotyledon perfusion experiments, reaching a concentration of 3.1 ± 0.4 µM in placental tissue. Final drug concentrations in the maternal and foetal reservoirs were 0.2 ± 0.05 and 0.08 ± 0.01 µM, respectively. Furthermore, crizotinib inhibited BeWo cell viability (IC50: 234 nM, 95% CI: 167–328 nM) 10 times more potently than other TKIs tested. In vitro transport studies revealed that crizotinib is a potent inhibitor of the transport activities of BCRP (IC50: 5.7 µM, 95% CI: 2.7–11.8 µM) and P-gp (IC50: 7.8 µM, 95% CI: 3.4–18.0 µM). In conclusion, crizotinib strongly accumulated in placental tissue at clinically relevant concentrations. IC50 values for transporter inhibition and trophoblast cell viability were similar to the tissue concentrations reached, suggesting that crizotinib can inhibit placental BCRP and P-gp function and possibly affect trophoblast viability.